Peculiarities of the postnatal physical development of the offspring of rats treated with aqueous plant extracts as an additional load - M. L. Temkin; O. N. Pavlova; O. N. Gulenko; E. N. Glazkova; E. S. Kanaeva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
Rats are attractive for various kinds of experiments aimed at studying the effect of substances on metabolism and other components of homeostasis. The use of biologically active substances of natural origin offers great opportunities for modulation of physiological processes in the body, increases the body's resistance, facilitates the clinical course of many environmentally caused diseases and has virtually no negative side effects. Purpose of the study: to study the peculiarities of postnatal physical development of the offspring of rats receiving intragastric aqueous plant extracts as an additional load. The experiment was carried out on sexually mature rats (50 females and 15 males), which were divided into 5 groups of 13 rats each. The groups received various compositions of aqueous plant extracts daily for 30 days at a dose of 30 mg/100 g of animal body weight. The animals were then mated, and the offspring were obtained and subjected to examination. Conclusion: loading rats with aqueous plant extracts promotes intensification of the postnatal physical development of the offspring, and the greatest efficiency is observed when using a mixture of aqueous extracts of Centella asiatica and Ginkgo biloba, rather than when using them separately.